PRODUCTION OF HUMAN INSULIN PRECURSOR IN A 10 LITER BIOREACTOR USING A METHANOL PULSE FEEDING - Dian Japany Puspitasari; Hendi Saleh Permana; Rudiyono Rudiyono; Anis Herliyati Mahsunah (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
ABSTRACT Indonesia as a country that had 19.5 million diabetic patients in 2021 is still importing raw materials of human insulin. The development of human insulin production process is needed to support the government’s objective to be independent in medicine aspect. Human insulin precursor (HIP) expressed from Pichia pastoris X33/pD902-IP had been developed and optimized in small-scale cultivation. However, the scaling up in bioreactor 10 L has not been studied. Using a 10 L-bioreactor the fermentation of P. pastoris X33/pD902-IP was developed. Fermentation was done in 120 hours using a basal salt medium (half concentration) for the vegetative and induction media. To induce HIP expression, methanol is fed by pulse strategy with a gradient concentration of 1-3% (v/v) for 48 hours. The dry cell weight (DCW) and HIP titers were 72 g/L and 286 mg/L, respectively. This development is the first fermentation of HIP expressed by P. pastoris X33/pD902-IP in a 10 L-bioreactor. ABSTRAK Indonesia sebagai negara dengan penderita diabetes 19,5 juta orang pada tahun 2021 masih mengimpor bahan baku insulin manusia. Pengembangan proses produksi insulin manusia diperlukan dalam rangka mendukung tujuan pemerintah untuk mandiri di bidang produksi bahan baku obat. Ekspresi prekursor insulin manusia oleh Pichia pastoris X33/pD902-IP telah dikembangkan dan dioptimalkan dalam skala kultur kocok. Akan tetapi, produksinya pada bioreaktor 10 L belum dilakukan. Untuk itu, fermentasi P. pastoris X33/pD902-IP dipelajari pada bioreaktor 10 L. Fermentasi dilakukan selama 120 jam dengan menggunakan media garam basal (setengah konsentrasi). Untuk menginduksi ekspresi HIP, metanol diberikan dengan gradien konsentrasi 1-3% (v/v) secara berkala selama 48 jam. Berat sel kering dan titer HIP masing-masing adalah 72 g/L dan 286 mg/L. Proses ini merupakan fermentasi pertama HIP yang dihasilkan P. pastoris X33/pD902-IP pada skala bioreaktor 10 L.